Manifestations of Islamophobia during COVID-19 (Challenges of the Future, 2022)
Background and Originality: Did the level of Islamophobia increase during the COVID-19, and in what forms did Islamophobia manifest during the mentioned period mentioned? This article aims to find out, through a systematic review, how Islamophobia has manifested during the COVID-19 and in in what forms did Islamophobia manifest during the mentioned period. The originality of the research is reflected in a thorough systematic review of the available literature in the field of Islamophobia at the time of COVID-19. The article's topic, which is relatively new and consequently under-researched, focused on examining the rise and manifestations of Islamophobia during the COVID-19 to identify relevant societal challenges to the emerging challenges.Method: A systematic review of Islamophobia during the COVID-19 was conducted in the following databases: Scopus, ProQuest Dissertations & Theses Global, Web of Science, Google Scholar, Base (Open Access), Springer Nature, JSTOR, ScienceDirect, SAGE, Wiley Online Library, and Emerald. Additional articles from other sources were identified by examining reference lists of studies found during database searches.Results: Based on inclusion and exclusion criteria, our systematic review found 19 articles published in English between January 2020 and January 2022. We found that the level of Islamophobia jumped during the COVID-19 and that Islamophobia shifted to online media during the strict lockdown but remained present in physical form.Society: Although the implications of the research for organizations are indirect, knowledge of the manifestations of Islamophobia during the COVID-19 may provide employers with an understanding of the plight of Muslims employed in organizations and enable them to take specific measures to alleviate the psychological distress of their Muslim employees.It is important for society to work for peaceful coexistence and mutual understanding in a pluralistic, democratic society and to make additional efforts to reduce the level of Islamophobia (in whatever form), hate speech and hate crimes against Muslims and to condemn all forms of discrimination and persecution against Muslims.Limitations / further research: As a limitation of our study, we must point out the relatively small amount of relevant literature on the studied topic, which is due to the relatively short period of study of Islamophobia in the COVID-19 period. We suggest that for further research, researchers should also focus on the manifestation of Islamophobia during the COVID-19 period in physical form, as the various research studies that we were able to find and evaluate for this systematic review focused mainly on the online implications of Islamophobia.
Keywords: COVID-19; Social media; Physical attacts; Systematic review; Hate speech; islamofobija